EFL TEACHERS’ PERSPECTIVE ON USING CHATGPT TO TEACH READING: A SYSTEMATIC REVIEW - Rizky Tri Ardiyani Ardiyani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Nowadays, there is an increase in the use of digital tools by English teachers to support reading instructions. Among these tools, Artificial Intelligence (AI) has become popular because it can help students understand texts more easily. This study aims to find out EFL teachers’ views on using ChatGPT in teaching reading. To achieve that goal, the study uses a systematic review method by collecting and analyzing fifteen journal articles related to this topic. The review analysis results showed that ChatGPT has some benefits for the reading task, such as making reading more interesting, helping students understand difficult texts, and giving flexible feedback to support their learning. However, the study also found some problems when teachers used ChatGPT to teach reading. Teachers worry that students might rely too much on ChatGPT, which could weaken their independent reading and critical thinking skills. They are also concerned that some AI-generated information may be inaccurate and that not all teachers feel confident or fully prepared to use ChatGPT in the classroom. This study is expected to give teachers, researchers, and schools a better understanding and ideas on how to use and maximize the potential of ChatGPT to teach EFL reading skills.